ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN POSYANDU UNTUK MENINGKATKAN STATUS GIZI LANSIA - Jon Piter Sinaga; Julpan Pasaribu (JURNAL KESMAS DAN GIZI (JKG), 2018)
Intergrated Service Post is a community activity in the effort of health service. Intergrated Service Post for elderly is the center of community activity in the effort of health service in elderly. Intergrated Service Post as a forum of activities that nuance community empowerment will run well and optimal if there is the process of leadership, organizing process, the existence of group members and cadres and the availability of funding. This study aims to analyze factors related to Utilization of Intergrated Service Post To improve Elderly Nutrition Status. The type of study is quantitative by using cross sectional approach. The population in this study were all elderly enrolled in Intergrated Service Post elderly of Sipea pea Public Health Center, West Sorkam Subdistrict that amounted to 54 elderly people and it started from January to March 2018. Samples amounted to 54 people with Saturated Sample method or the entire population. Data analysis included univariate, bivariate and multivariate. The results showed that respondents who use Intergrated Service Post 81.5% and 18.5% who did not utilize the Intergrated Service Post. There is a relationship of knowledge, elderly attitude, family support, and support of health officer with Intergrated Service Post utilization to improve nutritional status of elderly, with p value <0,05 for all four variables. The most influential variable is family support with OR value of 6,755. As well as advise the Intergrated Service Post officers to continue socialization to the community, especially elderly about Intergrated Service Post program and obey the Technical Guidelines appropriately and wisely.